1992
DOI: 10.1111/j.1550-7408.1992.tb04838.x
|View full text |Cite
|
Sign up to set email alerts
|

Action Spectra for Step‐Up Photophobic Response in Blepharisma

Abstract: The cells of Blepharisma which possess red pigment (blepharismin) show step‐up photophobic response (temporal ciliary reversal induced by a sudden increase in light intensity). Bleaching of the cells by cold shock raised a threshold light intensity for the response, Oxidation of red pigment that produced blue pigment did not raise the threshold for the response. The action spectrum for the step‐up photophobic response of the cells which possess normal red pigment had peaks at about 580, 540 and 490 nm, a value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

1993
1993
2017
2017

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(27 citation statements)
references
References 18 publications
2
25
0
Order By: Relevance
“…Very recently the structure of oxyblepharismin (OxyBP), the photoreceptor pigment mediating step-up photophobic responses in B. japonicum blue cells (7)(8)(9), has also been determined (10). The proposed molecular structure of oxyblepharismin, resulting from a photoinduced rearrangement and irreversible dehydrogenation of blepharismin, adequately accounts for the resemblance between its absorption spectrum and those of hypericin (HYP) and ST (10) (Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Very recently the structure of oxyblepharismin (OxyBP), the photoreceptor pigment mediating step-up photophobic responses in B. japonicum blue cells (7)(8)(9), has also been determined (10). The proposed molecular structure of oxyblepharismin, resulting from a photoinduced rearrangement and irreversible dehydrogenation of blepharismin, adequately accounts for the resemblance between its absorption spectrum and those of hypericin (HYP) and ST (10) (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…As far as the functional properties of these photoreceptor pigments are concerned, several experimental lines of evidence have indicated that a light-driven proton translocation process is involved in the early steps of the photosensory transduction chain in both B. japonicum and S. coeruleus (7,(12)(13)(14) and references therein). These findings suggest that protons could be released from the first excited singlet state of the chromophore (14,15), but this hypothesis had to be modified as the results of time resolved fluorescence measurements did not support it (16,17).…”
Section: Introductionmentioning
confidence: 99%
“…1 ) [2]; these granules are located just beneath the plasma membrane [3,4]. The pigments are considered to function as photoreceptors modulating the photobehavior of the cell [5,6]. Blepharismins have also been reported to be toxic to certain other kinds of protozoa [2] and to kill a variety of protozoa, including predators which actively feed on Blepharisma [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, ciliates may need to escape illuminated areas for survival (Matsuoka et al 2010). Additionally, blepharismin is believed to function as a photoreceptor, mediating photodispersal (Scevoli et al 1987, Matsuoka et al 1992, Checcucci et al 1993. What is the ecological significance of photodispersal in C. cucullus?…”
Section: Resultsmentioning
confidence: 99%